Response of Source-Sink Characteristics and Rice Quality to High Natural Field Temperature During Reproductive Stage in Irrigated Rice System - Tu, Debao; Jiang, Yang; Salah, Akram; Cai, Mingli; Peng, Wei; Zhang, Lijuan; Li, Chengfang; Cao, Cougui (Frontiers in Plant Science, 2022)
Global warming greatly affects the development of rice at different growth stages, thereby deteriorating rice quality. However, the effect of high natural field temperature during reproductive stages on rice quality is unclear. Thus, grain filling dynamics, source-sink characteristics and quality-related traits were compared between two contrasting natural field temperature conditions namely normal (low temperature) (LRT) and hot (high temperature) growth season (HRT) during reproductive stage. Compared with LRT, HRT significantly increased chalky grain rate (about 1.6–3.1%), chalkiness level (about 4.7–22.4%), protein content (about 0.93–1.07%), pasting temperature, setback, and consistence, and decreased total starch content (about 4.6–6.2%). Moreover, HRT significantly reduced the leaf area index (LAI, about 0.54–1.11 m2 m–2), specific leaf weight (SLW, about 1.27–1.44 mg cm–2) and source-sink ratio (leaf-sink ratio and/or stem-sink ratio), shortened the active grain filling period by 3.1–3.2 days, and reduced the rations of dry matter translocation to grain (RDMs). In conclusion, we suggested that significant reduction in assimilate translocation after flowering, resulting in the reduced active grain-filling duration and the poor rice quality (high chalkiness and the poor eating and cooking quality), modulated by source-sink characteristics in response to high natural field temperature during reproductive stage. These results enriched the study of high temperature-stressed rice and served as an important reference for selecting high-quality, heat-tolerant varieties and protecting rice quality under high-temperature conditions.